Comparison of 3 T and 1.5 T MRI in the evaluation of epilepsy - D. Runkauskaitė; T. Liakina; R. Mameniškienė (Neurologijos seminarai)
Background. Epilepsy is the fourth most common neurological disorder characterized by a long-term tendency to generate epileptic seizures due to excessive or synchronous activity in the neurons in brains. Most patients achieve adequate seizure control by taking antiepileptic drugs and have a good medication effect, however 20–30% of patients continue suffering from recurrent epileptic seizures. Magnetic resonance imaging (MRI) is the most basic and informative neurovisual approach for the diagnosis of epileptogenic foci and their types. A detailed neurovisual examination of the brain is particularly important in patients with refractory epilepsy who may be considered as option candidates for surgical treatment. Materials and methods. 164 patients (99 women and 65 men) were enrolled in the study who underwent 1.5 T MRI and 3 T MRI at Radiology and Nuclear Medicine Centre of Vilnius University Hospital Santaros klinikos. The pathological findings and the frequency of their detection with different magnetic field strengths of MRI were evaluated. Results. A statistically significant relationship (p<0.001) was found between magnetic field strength of MRI examination and the frequency of detecting pathological findings, but there was no statistically significant relationship (p=0.183) between magnetic field strength of MRI and the frequency of determining the type of epileptogenic foci. Conclusions. 3 T MRI more often and more accurately detects pathologies associated with epileptic seizures therefore it is recommended for patients with epilepsy or for those patients in whom the previous 1.5 T MRI could not identify pathology or showed mixed results.